Adiposity: A Seed of Depression - Dhivya Selvaraj; Pramod Kumar Pandey; Tunjin Vashisth; Sukanya Gangopadhyay; Usha Bindal; Kuldip Kumar (Proceedings)
Introduction: Depression is a very common psychological problem observed all around the world. Though various treatment modalities are available for this mental illness, further research is warranted to find novel therapeutics. Recent speculations on the role of adiponectin in animal models of depression have shown interesting results. Leptin is an adipokine that affects mood and cognition. Hence, the role of adiponectin and leptin in patients with depression needs to be probed. Objective: To estimate serum adiponectin and leptin concentration in depressive patients and compare them with healthy controls. Methods: This study was conducted at the Department of Biochemistry and Psychiatry, VMMC, and Safdarjung Hospital, New Delhi, following ethical clearance from our institution’s Ethics Committee. Serum samples were taken from 30 severely depressive patients and 30 healthy controls subsequent to receiving written consent from the patients’ relatives. The samples were checked for serum adiponectin and leptin levels via QUAEE-BIO and a DBC ELISA kit. Data were analyzed using SPSS version 21.0. Results: Cases and controls were age- and sex-matched. Serum adiponectin levels in the depression group were significantly higher than in the controls [Z = −2.18, p = 0.03]. Serum leptin levels in the depression group were not significantly different from that of the controls [Z = −0.47, p = 0.64]. Also, there was no correlation between serum adipokine levels and the severity of depression. However, there was a significant difference in adipokine levels between sexes in the case group and in the whole study group (p = 0.000). Conclusions: The higher serum adiponectin levels in the case group are in contrast with previous studies, which found lower adiponectin levels in depression. This may be due to the effect of treatment in cases of depression; further large-scale studies should be carried out to elucidate the role of adiponectin in depression. The small study size and absence of data about pretreatment serum adiponectin levels are the major limitations of this study.